Pendampingan Pengukuran Arah Kiblat di Musollah Kafe Ruumi Mengunakan Metode Astronomi - Alamsyah, Alamsyah; Risal, Risal; Rufaida, Erty Rospyana (Abdurrauf Journal of Community Service, 2024)
The determination of the Qibla direction is a crucial aspect of Islamic worship, particularly in the performance of prayer. In Indonesia, issues regarding inaccurate Qibla directions in mosques and prayer rooms have been identified, especially following the issuance of fatwas by the Indonesian Ulema Council (MUI) in 2010. This study aims to assist in measuring and verifying the accuracy of the Qibla direction at the Musollah of Ruumi Café in Makassar, Indonesia, using astronomical methods. Measurements were conducted from August 15 to August 22, 2024, using the Istiwa'aini tool. The results indicated a deviation of 12 degrees from the correct Qibla direction, with a measured azimuth difference of 342°37'03.94". The estimated error in distance is 1332 km from the southern direction of the Ka'bah. This deviation is significant, emphasizing the importance of accuracy in determining the Qibla direction for the validity of prayer. The study concludes that adjusting the Qibla direction at Musollah Ruumi Café is necessary to ensure that prayers are performed in accordance with Islamic law. The application of astronomical methods provided reliable and accurate results for further corrections.  Abstrak: Penentuan arah kiblat merupakan aspek penting dalam ibadah Islam, terutama dalam pelaksanaan salat. Di Indonesia, masalah ketidakakuratan arah kiblat di masjid dan musollah telah teridentifikasi, terutama setelah diterbitkannya fatwa Majelis Ulama Indonesia (MUI) pada tahun 2010. Penelitian ini bertujuan untuk membantu mengukur dan memverifikasi akurasi arah kiblat di Musollah Kafe Ruumi di Makassar, Indonesia, dengan menggunakan metode astronomi. Pengukuran dilakukan dari tanggal 15 hingga 22 Agustus 2024, menggunakan alat Istiwa'aini. Hasil pengukuran menunjukkan adanya deviasi sebesar 12 derajat dari arah kiblat yang benar, dengan selisih azimut yang terukur sebesar 342°37'03.94". Perkiraan kesalahan jarak adalah 1332 km dari arah selatan Ka'bah. Deviasi ini cukup signifikan, yang menekankan pentingnya akurasi dalam menentukan arah kiblat untuk keabsahan salat. Penelitian ini menyimpulkan bahwa penyesuaian arah kiblat di Musollah Kafe Ruumi perlu dilakukan untuk memastikan bahwa salat dilaksanakan sesuai dengan hukum Islam. Penerapan metode astronomi memberikan hasil yang dapat diandalkan dan akurat untuk perbaikan lebih lanjut.